Improvement of an enzyme-linked immunosorbent assay for equine herpesvirus type 4 by using a synthetic-peptide 24-mer repeat sequence of glycoprotein G as an antigen - BANNAI, Hiroshi; NEMOTO, Manabu; TSUJIMURA, Koji; YAMANAKA, Takashi; MAEDA, Ken; KONDO, Takashi (Journal of Veterinary Medical Science, 2016)
To increase the sensitivity of an enzyme-linked immunosorbent assay (ELISA) for equine herpesvirus type 4 (EHV-4) that uses a 12-mer peptide of glycoprotein G (gG4-12-mer: MKNNPIYSEGSL) [4], we used a longer peptide consisting of a 24-mer repeat sequence (gG4-24-mer: MKNNPIYSEGSLMLNVQHDDSIHT) as an antigen. Sera of horses experimentally infected with EHV-4 reacted much more strongly to the gG4-24-mer peptide than to the gG4-12-mer peptide. We used peptide ELISAs to test paired sera from horses naturally infected with EHV-4 (n=40). gG4-24-mer ELISA detected 37 positive samples (92.5%), whereas gG4-12-mer ELISA detected only 28 (70.0%). gG4-24-mer ELISA was much more sensitive than gG4-12-mer ELISA.